Ag-Innovation Data Hub - Cropping Calendar Tool - Wilson, Michael; Dalaa, Mustapha Alasan; Tepa Yotto, Ghislain (2025)
This info graphic presents the cropping calendar tool integrated into Ghana's Ag-innovation data hub (AIDH) enabling farmers to plan, track and optimise the cropping season with weather information and associated agro-advisories.